If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + -1X = 2X + 8 Reorder the terms: 23 + -1X = 8 + 2X Solving 23 + -1X = 8 + 2X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2X' to each side of the equation. 23 + -1X + -2X = 8 + 2X + -2X Combine like terms: -1X + -2X = -3X 23 + -3X = 8 + 2X + -2X Combine like terms: 2X + -2X = 0 23 + -3X = 8 + 0 23 + -3X = 8 Add '-23' to each side of the equation. 23 + -23 + -3X = 8 + -23 Combine like terms: 23 + -23 = 0 0 + -3X = 8 + -23 -3X = 8 + -23 Combine like terms: 8 + -23 = -15 -3X = -15 Divide each side by '-3'. X = 5 Simplifying X = 5
| 6n+3=7+2n | | x=2x^2+8x+10 | | 2x^2-100x+800=0 | | -m-4=-4 | | 4-5c=64 | | 10x^2+10=0 | | 6x^2+132x+726= | | -9-36=72 | | =x(16-2x)(21-2x) | | 2a^3+22a^2+60a= | | 8x^2-14x=-5 | | 16-2x=21-2x | | 8-m=21 | | 5z+6=-2z+27 | | -10-k=36 | | x^3+2x^2+3x+6= | | x=1x+7 | | 6a+8=20 | | 2x+5=8x+24 | | w^5+8w^3+16w-5=0 | | x^2+50=10x | | w^5+8w^3+16w=5 | | -4x^2+9x-8=0 | | w^5+8w^3+16w=0 | | 2=1+3(m+3) | | 26=4x-8 | | 90-2x=25x+24 | | w^2+10w-168=0 | | (0.8)x+4=19 | | -16g+-8g+17g=-14 | | 7x^2+12x-2=0 | | 2lnx+lnx^2=3 |